PENYELENGGARAAN PROGRAM BINA KELUARGA LANSIA (BKL) DI WILAYAH PERKOTAAN: POTRET PERMASALAHAN KLASIK - Sari Seftiani; Deshinta Vibriyanti (Research Centre for Population, Indonesian Institute of Sciences, 2020)
In 2045, population projection shows that one of five Indonesians is elderly. They are considered as a vulnerable group in terms of physical, economic, social-environmental and psychological challenges. Family plays a vital role in supporting an older person to overcome these challenges. Indonesia government has also developed a program to support the elderly population and their family through the initiation of Bina Keluarga Lansia (BKL) program. However, the implementation of this program is facing many obstacles at various levels. This paper aims to analyze the challenges that occur in the implementation of the BKL program, especially in urban areas. This paper based on the results of research conducted in Medan, Surabaya, and Mataram. Data and information gained through interviews, focus group discussion (FGD), observation, and literature review. The study found that the major problem of BKL is the lack of participation of the elderly group and their families due to various factors, particularly related to the format of the program’s activities. Integration of other aged person programs can be a solution to increase the involvement in the BKL program. Moreover, the strong commitment of the local government in improving the welfare of the elderly group is needed to support the program’s successfulness.